2015
DOI: 10.1089/ten.tea.2014.0367
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Total Human Bone Marrow Fraction in a Direct Three-Dimensional Expansion Approach for Bone Tissue Engineering Applications: Focus on Angiogenesis and Osteogenesis

Abstract: Current approaches in bone tissue engineering have shown limited success, mostly owing to insufficient vascularization of the construct. A common approach consists of co-culture of endothelial cells and osteoblastic cells. This strategy uses cells from different sources and differentiation states, thus increasing the complexity upstream of a clinical application. The source of reparative cells is paramount for the success of bone tissue engineering applications. In this context, stem cells obtained from human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 74 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…Regardless of the method used to add cells to the 3D scaffolds, vascularization remains a great challenge in tissue engineering. The addition of endothelial progenitor cells would be a possible approach to initiate vasculogenesis before implantation . Also, PLA is often used in association with calcium phosphate particles to improve bone regeneration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the method used to add cells to the 3D scaffolds, vascularization remains a great challenge in tissue engineering. The addition of endothelial progenitor cells would be a possible approach to initiate vasculogenesis before implantation . Also, PLA is often used in association with calcium phosphate particles to improve bone regeneration .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of endothelial progenitor cells would be a possible approach to initiate vasculogenesis before implantation. 37 Also, PLA is often used in association with calcium phosphate particles to improve bone regeneration. 23 Scaffolds loaded by calcium phosphate nanoparticles could be used to promote osteoblast activity and bone tissue formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the up‐regulation of Cx43 observed when HBMSCs were cultured in the presence of 10panx1, could probably compensate for an eventual regulatory effect of this specific inhibitor. Indeed, the role of Cx43 in osteoblastic differentiation of MSCs is well established (Guerrero et al, ; Plotkin, ; Plotkin, ) and its overexpression might sustain the expression of the bone‐specific markers and therefore compensate for any effect drawn by 10panx1. Nonetheless, both inhibitors in 2D reduced Panx1 gene expression at 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, scaffolds present favourable physicochemical cues, with macro and microstructures, providing a relevant 3D microenvironment for the promotion of cell communication and cell differentiation. Our previous studies, focusing on bone tissue engineering, have shown the promotion of bone cell differentiation when using polysaccharide‐based matrices (Guerrero et al, ). These natural structures hold promise for the regeneration of damaged tissues, because they are highly permeable and therefore facilitate the transport of nutrients and metabolites (Khan & Ahmad, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also neutral, non-toxic, non-immunogenic and non-carcinogenic, along with Food and Drug Administration (FDA) approved for a variety of applications 28 29 . Thus, it has been widely explored recently for various biomedical applications, such as drug and gene delivery 30 and tissue engineering 31 32 33 34 35 . For example, Ali Khademhosseini et al .…”
mentioning
confidence: 99%